Analytical studies of 19th century photographs by non-destructive techniques - Peres, M. (2013)
The late 19th century photographs are chemically a multilayer material of inorganic and organic compounds. A wide variety of chemical composition can be observed as consequence of the large number of photographic processes and products that were used as well as due to the ageing effects. The knowledge of the chemical composition of a photographic print can be very useful in determining its age and authenticity and the adequate restoring techniques or storage protocols. Most of the conservation work was done based on artistic evaluation; nevertheless, during the last decade, non-destructive analytical techniques have been associated with microscopic and visual methods for the identification and conservation of photographs and photographic emulsions. This work presents the analytical studies performed on two selected 19th century photographs; a non-destructive multi-technique approach was used to determine the composition and degradation status of the selected photographic samples.